Holy Trinity Cathedral, Port of Spain, Trinidad, B.W.I. - (:unkn) unknown (D. Adamson, Stationer, Port of Spain, 2010)
Image depicts a view of the Holy Trinity Cathedral, located in the capital city of Port of Spain, on the island of Trinidad, the Republic of Trinidad and Tobago. This is a view of the building from the corner of Hart and Abercromby Streets, looking south eastward.
Colour: Black and white; Style: Landscape; Other: Unbordered, Undivided.
Keywords: Trinidad and Tobago; Postcards; Cathedrals--Trinidad and Tobago; Church buildings--Trinidad and Tobago; Church architecture--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--Port of Spain